Spreading scientific knowledge in China: personalized social media influence elements - Li, Mengyu; Wang, Yao; Yasin, Megat Al Imran; Hashim, Norliana; Ang, Lay Hoon; Kang, Hongzhe (Hindawi Limited, 2022)
China’s society continues to be shaped by social media, which is both inescapable and indispensable. Remarkably, the majority of Chinese firms and private organizations have achieved success by making use of the possibilities provided by social media platforms. Notwithstanding incredible successes via social media, the majority of Chinese social media users lack scientific understanding, and as a result, there is a deficiency in the dissemination and popularization of scientific information among users of Chinese social media platforms. To bridge this gap, this study investigates specific features of social media based on scientific knowledge and proposes a scientific information propagation framework characterized by individual impact characteristics such as personal message, personal branding, service mentality strategy, exciting content, accurate and authentic, real-time streaming, and exclusive events. Among these factors, personal branding acquired a factor score of 23%, real-time streaming acquired a factor score of 20%, and service attitude approach received a factor score of 19.5%. Similarly, real and authentic personal messaging had a factor score of 15.6%. From the outcomes, we anticipated that personal or individual impact elements, such as personal branding, might affect the diffusion and popularization of scientific information among Chinese social media users.